Investigation on the use of bandpass sampling technique to extract information from doppler ultrasound signals - Muhamad Kassim, Nur Hanis (2008)
Doppler ultrasound technology has been widely used in medical field. This signal is use to get the information about heart movements to check the sign of abnormalities. Demodulation technique has to be performed to extract information of the DUS signal. There are a few type of demodulation and one of the types is bandpass sampling technique. In preparation for further investigation on the performances of bandpass sampling technique, a hardware set-up was arranged to send the data out from the PC. In order to create DUS signal that has the same characteristic as the real signal from patient, the signal from PC is mix with Megahertz signal using mixer. After the signal has downconverted using bandpass sampling technique, the signal is then analysed to confirm that the correct signal is obtained.